DESIGN OF MATCHED SYSTEMS WITH PERSISTENT EXOGENOUS INPUTS - Satoh, Toshiyuki; Takahashi, Takehiko (IFAC Proceedings Volumes, 2002)
This paper presents a design method for matched systems that are subject to persistent exogenous inputs. The exogenous inputs are assumed to be limited in both magnitude and rate of change. On the basis of the convex optimization technique, a computational method for the approximate supremum absolute value of a regulated output is developed. The computational method is fully utilized in the design framework of the principle of matching. A simple design example is also given.